2020
DOI: 10.31011/reaid-2018-v.86-n.24-art.676
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Epidemiológico dos Transtornos Mentais na População Adulta no Brasil: uma revisão integrativa

Abstract: Esta  revisão  integrativa  objetivou  descrever  o  conhecimento  produzido  sobre  o  perfil  epidemiológico  dos  transtornos mentais na população adulta brasileira. O estudo contou com 12 artigos, selecionados na Biblioteca Virtual em Saúde. Os critérios de inclusão foram: artigos completos; no idioma português e no período 2007 a 2017. Os transtornos mentais foram mais prevalentes em mulheres, sendo mais comuns os transtornos de humor e neuroses. Enquanto as psicoses e uso de substâncias, forma mais encon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
2
5
0
13
Order By: Relevance
“…It is noteworthy that the higher prevalence in females may be related to women's vulnerability to hormonal, social and psychological factors, the ease of identifying and admitting psychological distress and seeking help from specialized treatment services. 2,[16][17] Regarding marital status, it was observed that most users in this study were single, similar to other investigations, 2,11,13,18 however, in PSCCBarbacena-MG and PSCC II of Candeias-BA, there was a prevalence of married or in a stable union. 12,15 It is evident that marital status related to mental disorders is a controversial subject in the literature, because while some studies found an association, others did not.…”
Section: Resultssupporting
confidence: 89%
“…It is noteworthy that the higher prevalence in females may be related to women's vulnerability to hormonal, social and psychological factors, the ease of identifying and admitting psychological distress and seeking help from specialized treatment services. 2,[16][17] Regarding marital status, it was observed that most users in this study were single, similar to other investigations, 2,11,13,18 however, in PSCCBarbacena-MG and PSCC II of Candeias-BA, there was a prevalence of married or in a stable union. 12,15 It is evident that marital status related to mental disorders is a controversial subject in the literature, because while some studies found an association, others did not.…”
Section: Resultssupporting
confidence: 89%
“…Mental disorders can be defined as a group of signs and symptoms that clinically affect physical, psychological, behavioral, and cognitive aspects of a person ( American Psychiatric Association, 2014 ). In some cases, they can cause long term incapacities, leading to impairments in people’s functioning and quality of life (QoL) and are responsible for 34% of the existing disabilities in the Americas ( Hiany et al, 2018 ; Pan American Health Organization, 2018 ). People with severe mental disorders may need permanent care and social support in the community ( World Health Organization and the Gulbenkian Global Mental Health Platform, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A literatura científica aponta o período gravídico-puerperal como a fase de maior frequência de transtornos mentais na mulher, pois envolve inúmeras alterações físicas, hormonais, psíquicas e de inserção social na vida, podendo, portanto, ter reflexos na saúde mental, sendo a depressão o transtorno de maior frequência nesse período. Estima-se que aproximadamente uma em cada cinco mulheres apresenta episódios depressivos durante a gravidez e pós-parto (Andrade;Viana;Silveira, 2006;Silva, 2017;Hiany et al, 2018).…”
Section: Resultsunclassified